Demonumentalization of a controversial public space to constitute a place with new embodied meanings. The case of Plaza Dignidad in Santiago de Chile - Rojas Cabezas, Cristian; Alvarado Villarroel, Juan Esteban (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Taking into consideration the difficulty that it is separating the public space from monuments placed there, we expose the different transformations that have taken place in the public space “Plaza Italia/Baquedano/Dignidad” in Santiago, Chile, during the different protests, also known as, “Estallido Social”, that took place in this particular spot during the lasts months of 2019. Moments in which both the collective pulsations of the popular masses and the measures employed by the State in an attempt of regaining institutional order, results in a sort of “post-patrimony” found in the action that the bodies and layers of action occurred during the exaltation and denigration of the patrimonial pieces pre-existent. Moreover, we discuss that this process of “de-monumentalization” builds a public space with the capacity of sheltering the manifestation of a social collective, and alter the traditional meaning of the relation between sculpture and place, this way, defying the previous vision of patrimonial safeguard as a value in itself.